Associations of chronic diarrhoea with non-alcoholic fatty liver disease and obesity-related disorders among US adults. Issue 1 (12th August 2019) - Shin, Andrea; Xu, Huiping; Imperiale, Thomas F
Abstract : Mechanisms explaining observed associations between diarrhoea and obesity or increased body mass index (BMI) are unclear. Objective: To assess associations of bowel patterns with BMI, metabolic syndrome (MS), non-alcoholic fatty liver disease (NAFLD) and other obesity-related disorders. Design: We performed a cross-sectional analysis of data from adults who completed bowel health questions for the 2005 to 2010 cycles of the National Health and Nutrition Examination Surveys. Relationships were examined using multinomial logistic regression. Confounding effects of demographics, smoking, alcohol and BMI were examined by sequential modelling. Results: Among 13 413 adults, weighted prevalence rates of constipation and diarrhoea were 8.9% and 6.6%, respectively. Mean BMI was associated with bowel patterns (p<0.001), and was higher with diarrhoea (30.3 kg/m 2 ) versus normal bowel patterns (28.6 kg/m 2 ) and with diarrhoea versus constipation (27.8 kg/m 2 ). NAFLD was more prevalent (ORs, 95% CI) in diarrhoea versus normal bowel patterns (OR=1.34, 95% CI 1.01 to 1.78) or constipation (OR=1.45, 95% CI 1.03, 2.03) in adjusted analyses. The higher prevalence of MS in diarrhoea versus constipation (OR=1.27, 95% CI 0.97 to 1.67) was not independent of BMI. Conclusions: These findings suggest an association between diarrhoea and NAFLD that is independent of BMI.